Presentación N°61 - Duarte Quapper, Klaudio (Última Década, 2023)
We welcome spring in the Southern Cone with our journal issue N°61. We are delighted with the variety of subjects that have been covered throughout the nine contributions, the interview and the two reviews; to our eyes, this is a good sign to state that the concerns raised by youth researchers in Latin America and Chile are being linked to the multiple aspects of youth lives, as well as to the questions that can be raised to observe the contemporary social dynamics and the youth factor present in all of them.